Life of mine pit design optimization in anticline coal deposits based on break- even stripping ratio and slope stability analysis - Sylvia Della; Eddy Ibrahim; Taufik Toha; Maulana Yusuf; Syamsul Komar; Rahmat Wahyudi Putra (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2026)
This study investigates how geological structure, economic limits, and slope stability can be integrated to optimize a Life of Mine (LoM) pit design in an anticline coal deposit. The objective is to determine an economically viable and technically safe pit design by evaluating pit shell alternatives using the Break-Even Stripping Ratio (BESR) and slope stability considerations. The study utilized secondary technical data from an existing mining project, including geological models, pit shell optimization results, mining cost parameters, geotechnical evaluations, mining constraints, and reserve estimates. No additional field investigation, numerical modeling, or recalculation of pit optimization and slope stability was performed. The anticline structure significantly influences seam geometry, overburden distribution, and stripping ratio characteristics. Pit shell evaluation was conducted using a BESR threshold of 5.8 bcm/ton. Among the evaluated alternatives, pit shell 4 was selected as the optimum design, generating approximately 61.51 million bcm of waste and 17.16 million tons of mineable coal, with an incremental stripping ratio of 5.04 and an accumulated stripping ratio of 3.58. Slope stability assessment indicated that several pit wall sections required geometry adjustments to meet safety requirements. The optimized LoM pit design resulted in a mineable coal reserve of 16.12 million tons. The findings demonstrate that integrating geological structure, BESR analysis, slope stability, and mining constraints is essential for producing a pit design that maximizes coal recovery while maintaining economic feasibility and operational safety in structurally complex coal deposits.